Physical activity and disability measures in chronic non-specific low back pain: a study of responsiveness - Morelhão, Priscila K; Franco, Márcia R; Oliveira, Crystian B; Hisamatsu, Thalysi M; Ferreira, Paulo H; Costa, Leonardo OP; Maher, Chris G; Pinto, Rafael Zambelli (SAGE Publications, 2018)
Objectives: To compare the responsiveness of disability measures with physical activity measures in patients with chronic low back pain (CLBP) undergoing a course of physical therapy treatment. Design: This is a prospective cohort study with two-month follow-up. Subjects: A total of 106 patients presenting with non-specific CLBP of more than three months duration were recruited. Main measures: Disability measures investigated were Quebec Back Pain Disability Scale and Roland Morris Disability Questionnaire. Physical activity measures analyzed include the Baecke Habitual Physical Activity Questionnaire and objective measures derived from an accelerometer (i.e. total time spent in moderate-to-vigorous and light physical activity, number of steps and counts per minute). Disability and physical activity measures were collected at the baseline and after eight weeks of treatment. For the responsiveness analyses, effect size (ES) and standardized response mean (SRM) were calculated. Correlations between the change in disability and physical activity measures were calculated. Results: Responsiveness for disability measures was considered to be large with ESs ranging from −1.03 to −1.45 and SRMs ranging from −0.99 to −1.34, whereas all physical activity measures showed values lower than 0.20. Changes in disability measures did not correlate with changes in physical activity measures (correlation coefficients ranged from −0.10 to 0.09). Conclusion: Disability measures were responsive after a course of physical therapy treatment in patients with CLBP. The lack of responsiveness in the physical activity measures might be due to the inability of these measures to detect change over time or the use of an intervention not designed to increase physical activity levels.
Keywords: Low back pain; physical activity; questionnaire; responsiveness